IMPLEMENTASI KEBIJAKAN ORGANISASI DAN TATA KERJA DINAS PEKERJAAN UMUM KABUPATEN SIGI - Idris, Hamdani (Katalogis, 2015)
Study was conducted with the aim to know the implementation of the policy of the regional districts sigi number 8 year 2010 on the organization and work procedures of public works department sigi district. Research method used is descriptive qualitative.The research is the office of public works district sigi road trans-bora biromaru sigi , informants in this research is as much as 6 ( six ) people, namely the head of public works department sigi district, secretary of public works department sigi district, head of the psd public works department sigi district, the head of the sub part of planning and reporting of public works department sigi district , commission deputy chairman of the council secretariat iii sigi district, commission secretary is the council secretariat sigi district. Data collection techniques include observation, interview, and documentation. Technical data analysis includes editing data, a categorization data, interpretation of data, the withdrawal of conclusion. This study using the theory george edward iii with aspects of namely aspects Â of a communication, the aspect of resources, the aspect of disposition or kecederungan, the aspect Â of bureaucratic structure.The results of the study showed the implementation of policy organization and administration of year public works agency kabupaten sigi is not optimal. To aspects of a communication, the disposition and bureaucratic structure already done however need to be increased again, on the aspect of resources because aspects of resources including the human resources is not completed.